2017
DOI: 10.18632/oncotarget.21006
|View full text |Cite
|
Sign up to set email alerts
|

Profile of differentially expressed Toll-like receptor signaling genes in the natural killer cells of patients with Sézary syndrome

Abstract: Sézary syndrome (SS), an aggressive and leukemic form of cutaneous T-cell lymphoma, usually results in shortened survival. Improving innate immunity in SS by targeting natural killer (NK) cells with Toll-like receptor (TLR) agonists could be an interesting modulatory strategy. We evaluated the NK cell populations in SS patients assessing activating and inhibitory receptors expression and profiled the differential expression of TLR signaling pathway genes in unstimulated NK cells and after TLR7/8 stimulation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
1
5
0
4
Order By: Relevance
“…Recently, an analysis of NK cells in peripheral blood showed no significant difference in the number of NK cells in CTCL versus healthy individuals [58]. This is in contrast with previous reports of decreased NK cell numbers in SS patients that suggested that their function may be increased by Toll-like receptor (TLR) stimulation [59]. On the other hand, higher numbers of circulating NK cells have been correlated with a poorer prognosis both in MF and in SS [58] and related to findings in another Th2-mediated disease, i.e., atopic dermatitis (AD), where NK dysregulation contributed to AD pathogenesis [60].…”
Section: Antitumor Response and Immune Evasionmentioning
confidence: 83%
“…Recently, an analysis of NK cells in peripheral blood showed no significant difference in the number of NK cells in CTCL versus healthy individuals [58]. This is in contrast with previous reports of decreased NK cell numbers in SS patients that suggested that their function may be increased by Toll-like receptor (TLR) stimulation [59]. On the other hand, higher numbers of circulating NK cells have been correlated with a poorer prognosis both in MF and in SS [58] and related to findings in another Th2-mediated disease, i.e., atopic dermatitis (AD), where NK dysregulation contributed to AD pathogenesis [60].…”
Section: Antitumor Response and Immune Evasionmentioning
confidence: 83%
“…The NKG2D is the main activating receptor of the NK cells, and it binds to major histocompatibility complex (MHC) class I homologs (MICA and MICB) and UL-16 binding proteins (ULPB)-1 to 5, that function as signals of cellular stress [57,58]. Upon binding to NKG2D ligand (NKG2DL) expressed in malignant cells, the NK cells attack by degranulation of perforin and granzyme and production of IFN-γ and TNF-α [14].…”
Section: Nk Cellsmentioning
confidence: 99%
“…Thus, these altered NK cells may be recognized by tumor-naïve NK cells and are killed (Figure 3) [59]. Other mechanisms that favor immune escape by malignant cells, besides the trogocytosis, are the down-regulation of NKG2D observed in NK cells from SS patients [58], and the reduced number of total NK cells and the cytolytic CD56 dim CD16 bright NK cells, while the immunoregulatory CD56 bright CD16 dim NK cells are preserved [60]. The downregulation of NKG2D may be due to TGF-β and metalloproteinases [61].…”
Section: Nk Cellsmentioning
confidence: 99%
“…Portanto, não se sabe até que ponto o estímulo ao sistema imune levando à neutrofilia na SS leva a uma resposta realmente efetiva (Fierro et al, 2011;Manfrere et al, 2017;Torrealba et al, 2017). Além disso, estudos mostram que a relação neutrófilos/linfócitos no sangue periférico pode estar aumentada em diversas neoplasias malignas hematológicas e sólidas (Cengiz et al, 2017).…”
Section: Biópsias Visceraisunclassified
“…Há também uma redução nos linfócitos NK (CD16+CD56+), e aumento da expressão de CD25 na SS. Além dos níveis mais baixos de células T citotóxicas CD8-positivas e de células NK observados neste estudo, são descritas alterações funcionais destas células, levando a um estado de imunossupressão por comprometimento da resposta imune inata (Manfrere et al, 2017;Torrealba et al, 2017). Já o aumento da expressão de CD25 nos pacientes com SS pode ser devido ao aumento de células T reguladoras, o que podem contribuir para o efeito supressivo na resposta imune destes pacientes (Heid et al, 2009).…”
Section: Imunofenotipagem Por Citometria De Fluxounclassified